Protocol for a Pilot Study on the Gut Microbiome and Cardiometabolic Risk Factors in Latinx Emerging Adults in Miami, Florida. (14th June 2022) - Briceno, Alexandra; Caldera, Fabiana; Giri, Narasimhan; Gutierrez, Margaret; Martinez, Sabrina; Stebliankin, Vitalii
Abstract: Objectives: Cardiovascular disease (CVD) is one of the leading causes of mortality among the Latinx population in the U.S. In recent years, an increased risk of CVD among young adults has been observed. During emerging adulthood, health behaviors are adapted that can affect cardiometabolic risk factors (CMRF) providing an opportunity for targeted prevention strategies. Research has highlighted an association between gut dysbiosis and elevated risk for CMRF such as obesity and type 2 diabetes. Miami-Dade county's population is predominantly Latinx, with the largest heritage groups being of Cuban and Colombian descent. We hypothesize that gut dysbiosis and reduced microbial diversity will be associated with elevated CMRF. Methods: The participants will be community-living young adults recruited from the Florida International University student body and the larger community of Miami-Dade County. This study follows a cross-sectional design to examine the relationship between cardiometabolic risk factors (obesity, body composition, blood pressure, fasting glucose, diet, physical activity, smoking, sleep, and alcohol) and gut microbiome profiles. Individuals are eligible if they are 18–22 years old, self-identify as being of Cuban or Colombian background, are willing to provide a stool sample, have not been on antibiotic treatment in the past 6 months, and do not have autoimmune conditions. Participants will complete two visits; an assessment visit to gather demographic and anthropometric data, and a collection visit where fecal samples are returned and blood pressure, fasting blood glucose and other exposures are assessed. Fecal samples will be collected using the OMNIgene-GUT kit and participants will complete two 24-hour recalls using the Automated Self-Administered Recall System (ASA24). To characterize intestinal bacteria, 16S ribosomal RNA (16S rRNA) sequencing will be performed. Results: N/A Conclusions: The findings of this study will expand the current knowledge on the relationship between CMRF and the gut microbiome in emerging adulthood. This knowledge is necessary for the development of targeted prevention strategies for Latinx young adults who are at high risk for metabolic syndrome and other CMRF. Funding Sources: NHLBI/SUNY Downstate Health Sciences University.